Relapse of Multiple Myeloma Presenting with Biliary Obstruction - Alan Coss; Chen Zhou; Michael F Byrne; Alan A Weiss (Canadian Journal of Gastroenterology)
Pancreatic infiltration is a rare feature of multiple myeloma. A case of a 74-year-old man presenting with symptomatic biliary obstruction two years after the original diagnosis of myeloma is described. Confirmation of pancreatic infiltration with myeloma cells was performed by endoscopic ultrasound-guided fine-needle aspiration. Biliary stenting was performed at endoscopic retrograde cholangiopancreatography. Resolution of the pancreatic mass and the associated biliary stricture was observed after radiation and chemotherapy.